Gestión de la calidad y su impacto en la satisfacción del cliente de la cooperativa de taxis san camilo de quevedo, 2023 - Almeida Morán, Lady Suleika (2025)
The general objective of this research was to analyze the impact of quality management on customer satisfaction at the San Camilo Taxi Cooperative in the Quevedo canton during 2023. A mixed quantitative and qualitative methodology was used. In the quantitative phase, surveys were administered to a sample of 382 users to evaluate dimensions such as reliability, empathy, responsiveness, safety, and tangible aspects, based on the SERVPERF model. In addition, 132 employees of the cooperative were surveyed, gathering information on internal practices related to quality management. In the qualitative phase, a semi-structured interview was conducted with two managers, complemented by non-participatory observation of the operating environment. The results showed that, while there is a predominantly positive perception regarding driver treatment, safety, and punctuality, weaknesses were also identified, such as a lack of ongoing training, limited use of technological tools, and the absence of systematic evaluation. It was also found that, although protocols exist, they are not known or applied by all employees. It is concluded that quality management significantly influences